Assessing the RNA integrity in dry seeds collected from diverse endangered species native to the USA - Tetreault, Hannah M.; Zingerman, Zoe; Hill, Lisa; Ibrahim, Shaimaa; Maschinski, Joyce; Heineman, Katherine D.; Walters, Christina (Frontiers in Plant Science, 2025)
IntroductionDry seeds do not show obvious signs of life and so testing for viability, health and life expectancy can be challenging. Usually testing seed quality involves adding water and measuring metabolic capacity or growth potential by vital staining or germination assays. Importantly, most laboratory seed tests are intended to assay immediate viability, while most genebanks need tests that predict seed performance in the distant future. All currently available assays require considerable a priori knowledge of germination conditions and seeds large enough to dissect. Germination conditions are often unknown for seeds produced from wild species and are an important criterion for seed testing.MethodsUsing standardized methods (i.e., commercially available kits) we tested the feasibility of adapting a new seed quality assay that measures RNA integrity and is promising for cultivated species, to seeds from wild species. Most of the 100 wild species we include are rare or endangered and in need of preservation through genebanking. To determine the feasibility of measuring RNA integrity in seeds from wild populations, we compared the quality of RNA extracted from seeds that were recently harvested to those of the same species that have been genebanked for 16 to 41 years, with various seed traits examined for interference with RNA extraction and characterization.ResultsWe demonstrate reliable characterization of RNA quality across a diverse group of plants, despite variation in germination requirements, seed morphology or composition. RIN (RNA Integrity Number) values were usually high across all samples and variables, attesting to both the quality of newly collected material as well as its maintenance under genebanking conditions. This study conclusively demonstrates the feasibility of reliably extracting and characterizing RNA from dry seeds collected from wild populations, regardless of a variety of seed traits and morphologies. Relationships between RNA quality and seed age and viability require further exploration.